2000
DOI: 10.1089/10430340050032384
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Production of Human Granulocyte Colony-Stimulating Factor in Nonhuman Primates by Transplantation of Genetically Modified Myoblasts

Abstract: Clinical use of human granulocyte-colony stimulating factor (hG-CSF) to treat various diseases involving neutropenia has been previously shown to (1) successfully increase circulating neutrophils, (2) reduce condition-related infections, and (3) cause few side effects in patients. To alleviate the symptoms of neutropenia, the patient must receive frequent injections of recombinant hG-CSF. Permanent ways to deliver stable levels of the molecule to the patient are being investigated. Among them, the transplantat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 46 publications
0
4
0
1
Order By: Relevance
“…1,2,4,5 While undoubtedly a vital component of development, the linkage of these two processes is obviously detrimental 12,13 to the use of myoblast transfer as a gene complementation approach for the treatment of muscular dystrophies 8 ± 11 and certain metabolic deficiencies. 36 Finding targets to manipulate that would allow abrogation of apoptosis without affecting differentiation could improve the efficacy of these approaches. We have shown that in skeletal myoblasts both differentiation and the accompanying apoptosis depend on the variables of cell density and time and that these variables are inversely related.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,4,5 While undoubtedly a vital component of development, the linkage of these two processes is obviously detrimental 12,13 to the use of myoblast transfer as a gene complementation approach for the treatment of muscular dystrophies 8 ± 11 and certain metabolic deficiencies. 36 Finding targets to manipulate that would allow abrogation of apoptosis without affecting differentiation could improve the efficacy of these approaches. We have shown that in skeletal myoblasts both differentiation and the accompanying apoptosis depend on the variables of cell density and time and that these variables are inversely related.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,4,5 While undoubtedly a vital component of development, the linkage of these two processes is obviously detrimental 12,13 to the use of myoblast transfer as a gene complementation approach for the treatment of muscular dystrophies 8 ± 11 and certain metabolic deficiencies. 36 Finding targets to manipulate that would allow abrogation of apoptosis without affecting differentiation could improve the efficacy of these approaches. We have shown that in skeletal myoblasts both differentiation and the accompanying apoptosis depend on the variables of cell density and time and that these variables are inversely related.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical trials, the implantation of primary myoblasts for therapeutic purposes into the leg and heart has been shown to be feasible ( Gussoni et al , 1997 ; Menasche et al , 2003 ). Based on these findings and encouraging experimental evidence, the use of transduced myoblasts has been proposed as a gene delivery system for clinical studies ( Moisset et al , 2000 ; Suzuki et al , 2001 ). An important safety‐related aspect is the possibility to control the expression of the transgene by being able to determine the expression level in vitro prior to implantation or by tetracycline regulation.…”
Section: Transduced Myoblasts As a Gene Delivery System For Therapeutmentioning
confidence: 99%